Overview of Nutritional Status in Babies in Kampong Jawa, Langsa City District, Langsa City in 2026 - Afifa; Nailul Azkiya; Rayhan (Athallah Publishing, 2026)
Children's health and growth can be effectively measured through indicators of infant nutritional status. The problem of malnutrition, both in the form of malnutrition and overnutrition, remains a crucial issue for public health because it risks inhibiting growth and development and triggering chronic diseases in the future. Therefore, it is necessary to map the nutritional status of infants in Gampong Jawa, Langsa City District, as a basis for making accurate nutritional intervention policies. This study was conducted to describe the nutritional status of infants in Gampong Jawa, Langsa City District, for the period of 2026. The objectives of this study consist of general objectives and special objectives, which are as follows. This study adopted a descriptive quantitative approach with a cross sectional design of 75 infant subjects. The instruments used include digital scales and microtoises for weight and height measurement, as well as observation sheets in the form of checklists. Data analysis was carried out univariate to present a picture of the frequency distribution and percentage values of the variables studied. Most of the babies had a normal nutritional status of 60.0%, while 20.0% of the babies were classified as thin, 6.7% were very thin, and 13.3% were obese. This shows that there are still babies with abnormal nutritional status both in the form of deficiency and overnutrition.